German embedded word order, dass distribution, the contrast with ob-interrogatives, and modal-particle distribution support treating German exclamatives as elliptical emotive-matrix structures and as non-interrogative emotive assertions. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
German embedded word order, dass distribution, the contrast with ob-interrogatives, and modal-particle distribution support treating German exclamatives as elliptical emotive-matrix structures and as non-interrogative emotive assertions.
iso-id: iso:argument:7WOI1vEn; sha256: sha256:7ab29c95a09396aea755a5cd8f05b7608f5cb8d7228fcedffa6f3ed276904265